Global forum on skills for work and life: post 2015 : 14 - 16 October 2014, Bonn, Germany - (:unkn) unknown (My University, 2015)
"The UNESCO-UNEVOC Global Forum 'Skills for Work and Life Post-2015' took up the vital topics of youth, skills and greening TVET in the context of the post-2015 development agenda. 2015 marks the end of the Education for All (EFA) initiative, and global and regional debates are sharpening the focus of discussions geared towards setting concrete recommendations on how thepost-2015 education agenda should look like, and how it will be coordinated, monitored and assessed. Technical and vocational education and training (TVET) and skills for lifelong learning feature prominently in these debates. The post-2015 education agenda is an integral part of the sustainable development agenda. UNESCO advocates an overarching education goal, which is 'to ensure inclusive, equitable quality education and promote lifelong learning for all'. Underpinned by this advocacy, the forum engaged over 200 stakeholders from 71 UNESCO Member States, including 80 participants from 62 UNEVOC Centres from around the world, in identifying concrete and coherent global directions, policy measures and programmatic interventions in the areas of youth employability, skills development, and greening skills and TVET, as vital to visualizing and preparing for TVET post-2015. This report summarizes the key discussions and observations during the Global Forum, and creates an understanding of TVET transformations, underpinned by the above issues, in the context of framing the post-2015." (Excerpt, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; G 2.5 Nachhaltigkeit; G 1.3.2.2 Übergänge; P 1.1 Jugendliche; Berufsbildung; Internationale Zusammenarbeit; Nachhaltige Entwicklung; Berufseinmündung; Jugendlicher; Lebenslanges Lernen